Association between SMN2 copy number and clinical characteristics of patients with spinal muscular atrophy with homozygous deletion of exon 7 of the SMN1 gene - Žarkov, Marija; Stojadinović, Aleksandra; Sekulić, Slobodan; Barjaktarović, Iva; Stojiljković, Olivera; Perić, Stojan; Keković, Goran; Drašković, Biljana; Stević, Zorica (Vojnosanitetski pregled, 2015)
Aim: The aim of this paper was to determine association between SMN2 gene copy number and disease phenotype of Serbian spinal muscular atrophy (SMA) patients with homozygous deletion of exon 7 of the SMN1 gene. Methods: Patients were identified using regional Serbian hospital databases. Investigated clinical characteristics of the disease were: patients’ gender, age at disease onset, achieved and current developmental milestones, disease duration, current age, and the presence of the spinal deformities and joint contractures. Number of SMN1 and SMN2 gene copies was determined using real time PCR. Results: Among 43 identified patients, 37 (86.0%) showed homozygous deletion of SMN1 exon 7. One (2.7%) of 37 patients had SMA type I with 3 SMN2 copies, 11 (29.7%) patients had SMA type II with 3.1±0.7 copies, 17 (45.9%) patients had SMA type III with 3.7±0.9 copies, while 8 (21.6%) patients had SMA type IV with 4.2±0.9 copies. There were progressive increase in the SMN2 gene copy number from type II towards type IV (p
Keywords: muscular atrophy; spinal; genetic diseases; inborn; chromosome aberations; serbia